CARDIAC PATHOPHYSIOLOGY: MECHANISMS AND IMPLICATIONS FOR TREATMENT - Razhabova Zebiniso Safarovna (Web of Journals Publishing, 2025)
Cardiac pathophysiology refers to the alterations in normal heart function due to structural, electrical, and biochemical changes, often resulting in the development of cardiovascular diseases such as heart failure, coronary artery disease (CAD), arrhythmias, and valvular disorders. The underlying mechanisms of these conditions involve complex interactions between cellular, molecular, and systemic factors. This paper aims to explore the various aspects of cardiac pathophysiology, including the roles of ischemia, inflammation, genetic predispositions, and cellular remodeling. Additionally, the article discusses the implications for treatment strategies in managing these diseases, highlighting advances in both pharmacological and non-pharmacological interventions.
Keywords: Cardiac Pathophysiology, CAD.